1966
DOI: 10.1007/bf03003441
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and metabolic effects of general Anaesthesia during spontaneous breathing, controlled breathing, mild Hypoxia, and mild Hypercarbia

Abstract: Vision is as necessary an element in scientific achievement as is the carefully controlled experiment.-Ernest Gellhorn, 1953 SOME OF TIIE NEUROENDOCRINE SUBSTANCES that play a prominent role in the central nervous system are found in the peripheral circulation. Their exact functions are not entirely clear, but it appears evident that alterations in their concentration in the circulating blood are associated with profound overt mental and physical changes, TM as well as possibly initiating sudden serious distur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1966
1966
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 79 publications
1
12
0
Order By: Relevance
“…38 Liver function investigations on human subjects revealed no impairment as judged by thymol turbidity, alkaline phosphatase, and bilirubin tests -the only abnormality found being a transient increase in Bromsulphalein retention, maximal on the third to fifth postoperative day.G, 156 We found that the cephalin-cholesterol flocculation test becomes positive in dogs after 90 minutes of anesthesia but returns to normal within a few days, and that there are no significant N ewer anestheties 657 changes in serum glutamic oxalacetic and serum glutamic pyruvic transaminase estimations. 57 The findings of others 38 are in substantial agreement with this, the slight and transitory hepatic impairment appearing to be similar in degree to that produced by diethyl ether, although some clinicians have advised caution in the use of the agent in the presence of pre-existing liver disease. In gross overdosage studies on dogs, which were also subjected to hypotension, hypoxia, and hypercarbia, Cale and co-workers 25 found water vacuolization of the hepatic cells at biopsy, which they regarded as nonspecific and reversible.…”
Section: Clinical Pharmacology and Therapettticssupporting
confidence: 56%
See 1 more Smart Citation
“…38 Liver function investigations on human subjects revealed no impairment as judged by thymol turbidity, alkaline phosphatase, and bilirubin tests -the only abnormality found being a transient increase in Bromsulphalein retention, maximal on the third to fifth postoperative day.G, 156 We found that the cephalin-cholesterol flocculation test becomes positive in dogs after 90 minutes of anesthesia but returns to normal within a few days, and that there are no significant N ewer anestheties 657 changes in serum glutamic oxalacetic and serum glutamic pyruvic transaminase estimations. 57 The findings of others 38 are in substantial agreement with this, the slight and transitory hepatic impairment appearing to be similar in degree to that produced by diethyl ether, although some clinicians have advised caution in the use of the agent in the presence of pre-existing liver disease. In gross overdosage studies on dogs, which were also subjected to hypotension, hypoxia, and hypercarbia, Cale and co-workers 25 found water vacuolization of the hepatic cells at biopsy, which they regarded as nonspecific and reversible.…”
Section: Clinical Pharmacology and Therapettticssupporting
confidence: 56%
“…53 , 77, 20G However, if excessive depth of anesthesia is avoided, pulmonary ventilation remains adequate as reflected by a minimal change in the arterial blood pH and PaC0 2 , and there is much less likelihood of developing metabolie acidosis than with diethyl ether. 53,57 Controlled respiration is easily achieved with fluroxene. 53 , 172 Cireulation.…”
Section: Inhalation Anestheticsmentioning
confidence: 99%
“…Thus, anesthesia may also complicate the data sets either because of a diminished signal or as a result of drug-drug interactions on brain systems. Anesthesia itself may also be stressful, for a number or reasons; (i) anesthesia is known to produce apoptopic changes in the brain’s of animals (Dong et al, 2009; Lu et al, 2010); and (ii) it is stressful in that it may raise cortisol levels and that simple immobility may not be a measure of conscious sensation in the animal (Dobkin et al, 1966; Oyama, 1973). Anesthetic depth levels have been measured in rats using thalamocortical local field potentials (Silva et al, 2010) – burst suppression ratio (% suppression during burst suppression pattern) used as an index of anesthetic depth occurred in the somatosensory cortex and thalamic nuclei with the highest concentration of isoflurane (1.7%).…”
Section: Animal Preparationmentioning
confidence: 99%
“…It has long been recognized that volatile anesthetic agents do not cause histamine release (36). An in vitro study compared histamine release by propofol, ketamine and thiopental from human MC of skin, lung and heart origin.…”
Section: Mast Cell Activation By Drugs Used In the Perioperative Periodmentioning
confidence: 99%